Proposed new interior design of Puteh Muslimah Centre for Juin Sdn. Bhd, at 39A, Jalan Sultan Ismail 50200 Kuala Lumpur / Nor Hatika Zakaria - Zakaria, Nor Hatika (2010)
This report is the coursework for subject INA 396 which is this thesis is a one of the requirements for Final Year Student to obtain their Diploma in Interior Design of Universiti Teknologi Mara. The project that had been chosen for the final project is to propose a New Interior Design of Puteh Muslimah Centre for Juin Sdn. Bhd at 39a,Jalan Sultan Ismail 50200 Kuala Lumpur. This proposed Muslimah centre is only suitable for all the women especially the Muslimah women. Besides the selling the collection of Puteh.this centre is also provided services such as hair salon, makeover and consultation. The products of the Puteh includes abaya,kaftan,headscarf,prayerwear and accessories such as the brooch. The target market for the users of this Puteh Muslimah Centre care Muslim women from all ages and classes. Concept and images that had been chosen for this project is also related with the product and client image.